2023
DOI: 10.1038/s41419-023-06211-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy remodels the tumor microenvironment for enhancing immunotherapeutic sensitivity

Senbo Liu,
Wenkang Wang,
Shengyun Hu
et al.

Abstract: Cancer immunotherapy has transformed traditional treatments, with immune checkpoint blockade being particularly prominent. However, immunotherapy has minimal benefit for patients in most types of cancer and is largely ineffective in some cancers (such as pancreatic cancer and glioma). A synergistic anti-tumor response may be produced through the combined application with traditional tumor treatment methods. Radiotherapy (RT) not only kills tumor cells but also triggers the pro-inflammatory molecules’ release a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 169 publications
0
5
0
Order By: Relevance
“… 21 28 In the present study, we evaluated the modulation of TCRβ repertoire in response to the combination treatment and found that the TCRβ clonality significantly increased and TCRβ diversity significantly decreased during this combination therapy in progressors ( figure 3 , B and D). It has been reported that radiotherapy and ICIs targeting PD-1 axis augmented the diversity of the TCR repertoire of tumor infiltrating lymphocytes, 29–31 and it was also reported that TCR repertoires of tumor infiltrating T cells were different from those in peripheral T cells, when responded to treatment. 32 33 Therefore, there is still controversy regarding the relationship between TCR repertoires and efficacy of the treatment, and the relationship between TCR repertoires in tumor infiltrating T cells and those in peripheral T cells.…”
Section: Discussionmentioning
confidence: 99%
“… 21 28 In the present study, we evaluated the modulation of TCRβ repertoire in response to the combination treatment and found that the TCRβ clonality significantly increased and TCRβ diversity significantly decreased during this combination therapy in progressors ( figure 3 , B and D). It has been reported that radiotherapy and ICIs targeting PD-1 axis augmented the diversity of the TCR repertoire of tumor infiltrating lymphocytes, 29–31 and it was also reported that TCR repertoires of tumor infiltrating T cells were different from those in peripheral T cells, when responded to treatment. 32 33 Therefore, there is still controversy regarding the relationship between TCR repertoires and efficacy of the treatment, and the relationship between TCR repertoires in tumor infiltrating T cells and those in peripheral T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional radiation therapy, the combination of a single, high ablative doses followed by subsequent lower doses, which can convert the immunosuppressive microenvironment to a more immunogenic one with increased in ltration of immune effector cells and a downregulation of regulatory T cells. 17,18,19,20 Indeed, in previous clinical studies, partial bulky-tumor irradiation was demonstrated to induce abscopal effects in patients. 21 For instance, SBRT-PATHY, a speci c radiation therapy developed for unresectable bulky tumors, exploits radiation-hypoxia-induced non-targeted effects like bystander effects and abscopal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral part of GTV surrounding the core STV is de ned as TTV (Transitional Treatment Volume) and the TTV essentially serves as a "cushion" between ablated target and surrounding tissue. Cancer cells in the peripheral TTV tend to be normoxic and warm in immune microenvironment, while a modest dose has the potential to upregulate the immune micro-environment 17 . This ultra-heterogeneous dose distribution serves multiple purposes.…”
Section: Concept Of Scartmentioning
confidence: 99%
“…Radiotherapy has been combined with CAR-T cells to avoid the tumor escape resulted from CAR-targeted antigen loss ( 108 , 109 ). Pre-exposure to radiotherapy could induce immunogenic cell death and antigen release, promote HLA or CAR target expression on tumor cells, increase APC activation and immune cell infiltration, thereby reshaping the TME to favor anti-tumor immune responses ( 108 , 110 , 111 ). It is worth of evaluating radiotherapy combining with CAR-Ms or CAR-Ns in future studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%